EFFECT OF ELECTROLYTE ON IONIC INTERACTIONS OF DILUTE SOLUTION OF POLY (VINYL ALCOHOL) AT DIFFERENT TEMPERATURES (Biological Sciences - PJSIR, 2002)
A viscometric method was used to determine the effect of sodium chloride on ionic interaction of dilute sol ution s of poly (vinyl alcohol) at different temperatures. Viscosities  of 0.1 to 0.5 g dl·1  polyvinyl  alcohol  solutions were measured  under the influence of  sodium chloride  (1 x  10·2 to 6 x 10·2 mo!. dm·3) at different temperatures (30 to 50 ± 0.1°C). Ion-ion and ion-solvent interactions were evaluated in terms of Jones Dole coefficient A and B respectively. Negative values of B-coefticient at 30 ± 0.1 °C show that sodium chloride behave as structure maker  in dil ute aqueous poly (vinyl alcohol) solution where as the positive values of B-coefticient reveals the average molecular weight of poly (vinyl alcohol). Activation parameters were also evaluated in terms of energy of activation (Eri*), change in free energy of activation (t.G*) and change in entropy of activation (t.S*) as a function of polymer composition , salt concentration and temperature.